The 2nd International Electronic Conference on Foods—“Future Foods and Food Technologies for a Sustainable 2021
DOI: 10.3390/foods2021-10930
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, and Practice of Home-Based Food Handlers in Hulu Selangor, Malaysia Regarding Food Safety

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…Similarly, another study found that people with low education had lower level of practice compared to the group with a high level of education [ 27 ]. This association was also supported by the conclusion from other study [ 28 ] Furthermore, knowledge is a factor associated with practice in our study. It suggests the potential role of regular training program to improve knowledge and practices among food caregivers because the trained individuals tend to emerge significantly higher knowledge compared to untrained food handlers [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, another study found that people with low education had lower level of practice compared to the group with a high level of education [ 27 ]. This association was also supported by the conclusion from other study [ 28 ] Furthermore, knowledge is a factor associated with practice in our study. It suggests the potential role of regular training program to improve knowledge and practices among food caregivers because the trained individuals tend to emerge significantly higher knowledge compared to untrained food handlers [ 18 ].…”
Section: Discussionsupporting
confidence: 92%